Literatur Review Tentang Manajemen Konflik: Sumber, Gejala, dan Dampak Konflik Dalam Organisasi - Desta A, Risda Dui; Sa’adah, Masrurotus; Nikmah, Tiara Iftitahun; Retha, Amalia Wanda Mega; Mualimin, Mualimin (FEB Universitas Maritim Semarang, 2024)
This article aims to provide theoretical and practical insights into conflict management to support leaders and managers in managing conflict effectively in various contexts and provide a comprehensive understanding of conflict management through a literature review of the sources, symptoms, and causes of conflict. Conflict that occurs in an organization can hinder the achievement of desired goals, therefore conflict needs to be managed properly so that its impact can be minimized, organizational conflict can also be interpreted as a conflict that arises when the goal-oriented behavior of one group conflicts with or is threatened by the goals of another group. This study uses a literature study method to analyze various concepts of conflict management that have been put forward by experts. The results of the study show that conflict, whether in a positive, negative, or neutral sense, is an unavoidable phenomenon. The source of conflict can come from various factors that trigger differences and clashes between individuals, groups, or organizations. Conflict also occurs due to misunderstandings or incompatibilities between individuals or groups in an effort to achieve their goals, this is often referred to as a causal factor. The impact of conflict actually depends on its nature. On the one hand, well-managed conflict can improve the quality of decisions, encourage active involvement in discussions, and strengthen group cohesion. However, on the other hand, conflict can also drain members' energy, disrupt productivity, and cause hostility that hinders collaboration. Abstract and Keywords must be written in English, in italic style, and contain a brief description of the research background, objectives, methods, findings, and implications. The abstract is written in one paragraph with a single space (maximum 200 words), without any reference or formula.